2022
DOI: 10.1080/15384047.2022.2051158
|View full text |Cite
|
Sign up to set email alerts
|

GANT61 suppresses cell survival, invasion and epithelial-mesenchymal transition through inactivating AKT/mTOR and JAK/STAT3 pathways in anaplastic thyroid carcinoma

Abstract: Glioma-associated oncogene (Gli) antagonist-61 (GANT61) not only suppresses the malignant behavior of several cancers but also presents synergistic effects with other anticancer agents on suppressing the progression of cancers, while relevant information is rare in anaplastic thyroid carcinoma (ATC). This study aimed to explore the therapeutic effect of GANT61 in ATC and its molecular mechanism. ATC cells (8505C and CAL-62) were treated with GANT61, followed by detection of cell proliferation, apoptosis, invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In vitro experiments showed that the inhibitory effect of CTX on cancer cell proliferation, migration, and invasion was negatively correlated with p-Akt levels. This implies that some downstream components of Akt that are related to migration and invasion, such as mTOR ( 26 )or Glycogen Synthase Kinase 3β (GSK3β)/Snail ( 27 ), may be inhibited by PD. In addition, CTX itself decreases CRC cell migration and invasion to a certain degree, which may interfere with other downstream pathways of EGF/EGFR ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments showed that the inhibitory effect of CTX on cancer cell proliferation, migration, and invasion was negatively correlated with p-Akt levels. This implies that some downstream components of Akt that are related to migration and invasion, such as mTOR ( 26 )or Glycogen Synthase Kinase 3β (GSK3β)/Snail ( 27 ), may be inhibited by PD. In addition, CTX itself decreases CRC cell migration and invasion to a certain degree, which may interfere with other downstream pathways of EGF/EGFR ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 8505C cells, heat shock protein 90, in combination with histone acetyltransferase inhibitor triptolide, reduced cell viability and increased cell death, possibly through the inactivation of mTOR pathway [ 39 ]. Similarly, the combination of baicalein and docetaxel, and glioma-associated oncogene antagonist 61, also appeared to induce anti-cancer effects in 8505C cells through the suppression of the mTOR pathway [ 40 , 41 ]. Contrastingly, metformin diminished the viability of 8505C and induced a slight increase in apoptosis; however, in this case, total mTOR expression was increased [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…LN229 control and PIKE-A knockdown cells were harvested and suspended in 1 mL of TRIzol (Invitrogen, Carlsbad, CA, USA). Then, dry ice was used to transport to Lc-Bio Technologies Co., Ltd. (Hangzhou, China), as described previously [ 28 ].…”
Section: Methodsmentioning
confidence: 99%